Factors Associated with Teenage Pregnancy and its Effects in Kibuku Town Council, Kibuku District, Eastern Uganda: A Cross Sectional Study - Manzi, Fred; Ogwang, Joshua; Akankwatsa, Allen; Wokali, Oliver Caroline; Obba, Francis; Bumba, Ahmed; Nekaka, Rebecca; Gavamukulya, Yahaya (Primary Health Care: Open Access, 2018)
The prevalence of teenage pregnancy in Kibuku District was reported to be 35.8% in 2016, higher than the average rate for rural areas in Uganda estimated at 27%. This study aimed at determining the factors associated with teenage pregnancy and its effects in Kibuku Town Council, Kibuku District. The research used a cross sectional study that employed both quantitative and qualitative methods. Researcher administered questionnaires were given to 180 teenagers in three randomly selected secondary schools in Kibuku Town Council while oral interviews were conducted to 40 pregnant teenagers and teenage mothers attending antenatal clinic at Kibuku Health Centre IV. Microsoft excel and SPSS were used to analyze the data and it was represented in form of frequency tables and figures. There was a big knowledge gap about reproductive health as 75% of school going teenagers believed the minimum age of conception was above 14 years. Bad peer groups, enticement with gifts and poverty were the most common causes of teenage pregnancy while school dropout at 48%, broken marriages and miscarriages at 9% were recorded as its major effects. In conclusion, teenage pregnancy remains a major problem in Kibuku Town Council, Kibuku District and needs urgent interventions which include encouraging parents and schools to adopt a culture of discussing sexual and reproductive health, advocating for abstinence and where necessary, contraception be made open and accepted without stigma.
Keywords: Teenage pregnancy; Adolescents; Sexual and reproductive health; School dropout